A COMPARATIVE STUDY ON THE CLEANING EFFICIENCY OF CONVENTIONAL AND ULTRASONICALLY ACTIVATED ENDODONTIC IRRIGANTS - Aureliana Caraiane; Gheorghe Raftu; Cristina Gabriela Pușcașu; Steliana Gabriela Buștiuc; Cristina Bartok-Nicolae; Claudia Elena Sion; Erdogan Elvis Șachir (Romanian Journal of Oral Rehabilitation)
Aim of the study: This study aimed to compare the effectiveness of four irrigation protocols in removing residual dentinal debris from root canal walls: citric acid, EDTA, a combination of sodium hypochlorite and EDTA, and sodium hypochlorite activated with ultrasound. Materials and Methods: A total of 40 extracted single-rooted permanent teeth were selected and randomly divided into four groups (n = 10) based on the irrigant and method used. After access cavity preparation, working length determination, and rotary instrumentation using the ProTaper system, canals were irrigated according to their group protocols. The teeth were then sectioned longitudinally and evaluated under an endodontic microscope. RDD was scored on a 3-point scale: 0 – absent, 1 – moderate, 2 – slight presence. Results: The combination of sodium hypochlorite and EDTA (Group 3) showed the highest efficacy, with 5 canals free of RDD and 5 with moderate presence. Ultrasonically activated sodium hypochlorite (Group 4) resulted in mostly moderate presence and one canal with no debris. EDTA alone (Group 2) and citric acid (Group 1) showed lower efficacy, with no canals completely free of debris. Conclusion: The combination of sodium hypochlorite and EDTA proved to be the most effective irrigation protocol. Ultrasonic activation of sodium hypochlorite showed improved results compared to citric acid and EDTA alone, but did not outperform the NaOCl–EDTA combination. These findings highlight the importance of using both effective chemical agents and proper activation techniques for optimal root canal debridement.